Pengaruh Etos Kerja, Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan PT Efrata Garmindo Utama di Sukoharjo - Anindia Dita Rachmadani; Lamidi Lamidi (Lembaga Pengembangan Kinerja Dosen, 2024)
PT Efrata Garmindo Utama Sukoharjo itself operates in the retail sector which makes batik clothes (men, women and children) with its flagship brand, namely Bateeq. This research is a survey with quantitative data, namely data on the number of employees and the number of respondents to the questionnaire. Primary data in this research is the result of distributing questionnaires given to employees of PT Efrata Garmindo Utama. The population in this study were all employees of PT Efrata Garmindo Utama, totaling 502 employees. The sample in this study was narrowed using the Slovin formula to 85 respondents using a purposive sampling technique. The data collection technique uses a questionnaire. Test research instruments with validity and reliability tests, classic assumption tests including multicollinearity tests, autocorrelation tests, heteroscedasticity tests and normality tests. The data analysis method uses descriptive analysis, multiple linear regression test, t test, F test and R² test. The results of the validity test for all instruments obtained a significance value = 0.000 < 0.05, meaning that all instruments were valid. Reliability test results for all reliable variables. The results of the multicollinearity test, autocorrelation test, heteroscedasticity test, normality test for all variables passed the test. The results of the multiple linear regression test obtained the regression equation Y = 17.062 + 27.571 X₁ – 47.771 X₂ + 0.013 The results of the t test for the work ethic variable have no significant effect on employee performance with ρ-value = 0.378 > 0.05. Work discipline has a significant effect on employee performance with ρ-value = 0.012 < 0.05. Work motivation has a significant effect on employee performance with ρ-value = 0.000< 0.05. The results of the F test show a calculated F of 34.876 with a ρ-value of 0.000 < 0.05, meaning that the model used to test the influence of the independent variables is variable X1 (work ethic), variable X2 (work discipline) and variable X3 (work motivation) on The dependent variable, namely employee performance (Y), is correct. The R² test results obtained a value (Adjusted R²) of 0.574, meaning that the contribution of the independent influence of variable X1 (work ethic), variable X2 (work discipline) and variable X3 (work motivation) to Y (employee performance) was 54.7%. The remainder (100% - 54.7%) = 45.3% is explained by other variables outside the model, for example quality of work life, workload, work environment, job satisfaction and leadership style.